Drwyahaji Pada Masa Pemerintahan Raja Jayasakti - Ayu Karmatriani, Ni Luh Putu; ., Zuraidah (Humanis; Vol 22 No 1 (2018), 2018)
This researcher focused on the inscription of the reign of King Jayasakti mentioning the sources of empire’s income (d?wyahaji). The existence of d?wyahaji collected by the king through officers and for the benefit of the community. The purpose of this research is to know the types of d?wyahaji and its collection system. This study uses several methods of data collection, data analysis and theory to solve problems. Methods of data collection used are literature study, observation, and interview. At the next stage is processed by using qualitative analysis of interpretative and comparative analysis. The theory used as the basis of reference in this research is, functional structural theory and theory of tax collection. The results of this study reveal that the types of d?wyahaji are bungan tangklik, puspusana, tarub, aspaspan, pasang gunung, and pangrama, with the mechanism of d?wyahaji collection of karaman¸ area officials and the king's treasury.